A companion to Richard Hooker - Kirby, W. J. Torrance (Brill's companions to the Christian tradition ;, 2008)
Richard Hooker was a learned philosophical theologian and engaged polemicist of the later sixteenth century who explained and defended the Elizabethan religious and political settlement.